Peran Kinerja Pegawai dan Kepemimpinan dalam Meningkatkan Kualitas Pelayanan Publik Studi pada Dinas Penanaman Modal dan PTSP Kota Solok - Yeni, Afni; Nurhayati, Nurhayati; Suriani, Fitri (JURNAL ADMINISTRASI KANTOR; Vol 13 No 1 (2025): Jurnal Administrasi Kantor (Juni 2025)DO - 10.51211/jak.v13i1.3388, 2025)
The following study aims to provide knowledge on employee performance and leadership style towards service quality at the Investment and PTSP Office of Solok City. The study category used is a quantitative approach with a total sampling technique, where the entire population consisting of 37 employees is used as a sample. Data were collected using a questionnaire. The technique for analyzing the data obtained is multiple linear regression analysis showing that employee performance and leadership style have an effect on service quality, t-test, and f-test. The results of this study note that: (1) employee performance has a significant impact on the independent variables at the Investment Model and PTSP Office of Solok City; (2) service quality has a significant impact on the independent variables at the Investment Model and PTSP Office of Solok City; and (3) leadership style and dependent variables have a significant and simultaneous impact on the independent variables at the Investment Model and PTSP Office of Solok City. In addition, the coefficient of determination test was 54.9%, then the remaining 45.1% was factored into other variables not included in this study, for example work experience, job rotation, and job satisfaction.   Keywords : Employee Performance, Leadership Style, Service Quality